Faça o que eu digo, mas não faça o que faço: convergências e divergências do discurso ambientalmente responsável dos consumidores e seu comportamento de consumo - Peixoto, Amanna Ferreira (2012)
Given the idea of rethinking the way society consumes, which is characterized by the abundance of consumer goods and at the same time begins to feel the close possibility of suffering with the impacts caused by the nature of consumerism, made the interest of investigating consumer habits related to environmental preservation to appear. It was noticed that the society has valued the sustainable practices even more, but how those people act as consumers before their apparent ethical stance they present? The consumers profess a concern on environmental questions but researches indicate that their consumer habits continue to be the same, the old ones. Thus, this study aimed to analyse the convergences and divergences between the environmentally responsible discourse and the consumers behaviour according to the theory of action of Argyris et al. (1985). From a qualitative approach, this research used in-depth interviews and a self-report through notes in a board diary to collect data about the environmentally responsible discourses and the consumers behaviours of 15 participants. To analyse data, the research used the dimensions related to the environmentally responsible research presented in Stern (1999, 2000): personal domain, behavioural domain, contextual domain, personal capabilities and habits and routines. The four first dimensions were investigated to identify the environmentally responsible discourses through interviews, and the last dimension habits and routines was investigated to identify the consumers behaviour effected by means of the registration of purchase experiences, consume and discard of goods in a board diary. The research suggests that the environmentally responsible behaviour is not always coherent with its discourse by the existence of motivational (impotence, lack of interest, sacrifice, convenience) and contextual elements (financial condition, absence of public policies, constraints of time and culture). It was noticed that environmentally responsible behaviour appear in some aspects of the participants daily lives, because it is understood that having quite favourable good consumer habits to the environment, under current conditions that the society lives, it would be impractical.